Problems of Lithuanian Mathematical Olympiad-2005 - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2023)
The questions of the Lithuanian olympiad-2005 are presented and solutions are given.
Keywords: olympiads; problems solving; recursion sequences